Exploring Learners’ Characteristics and Educational Practices and Proposing Four Learning Strategies: Case Study: Exploring Learners’ Characteristics and Educational Practices and Proposing Four Learning Strategies: Case Study - Dodi Widia Nanda (International Journal of Technology Vocational Education and Training, 2020)
The research’s purpose is to explore learners’ characteristics and educational practices. It is conducted because students’ characteristics and educational practices are multifaceted, depending on the setting. Therefore, this study employed a case study as the research methodology, utilizing observation in order to collect data concerning students’ characteristics and educational practices. The SDN Islam Moderenlocated in Kabupaten Dharmasraya, Indonesia, is selected as the research setting, precisely sixth grade comprising 15 students with seven male and eight female students aged between 10 to 11 years old. The result shows that there are two leaners’ characteristics found in the study; application directed learnersdan the level of motivation (intrinsic and amotivation), while play based-learning, technological use, and outdoor learning activity are the three educational practices found in this study. Multisensory instruction, peer-feedback, simulated conversation strategy, and collaborative work are the proposed learning strategies in this research in order to enhance and promote the teaching and learning process in this case study.